Histopathological evaluation of effects of high fructose diet on bone healing in tibial defects: An Experimental study - Kaya, Can Ayhan; Sagsoz, Asli; Tanrisever, Murat; Gelic, Turker; Ozercan, Ibrahim Hanifi; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
The purpose of this study was to examine the impact of a high-fructose diet on bone regeneration in defects created in rat tibias. The experimental setup was performed with 24 female Sprague-Dawley rats in the same estrus period; the rats were divided into two groups as control and experimental groups. In the control defect group (n=12), a cylindrical defect of 4 mm in diameter and 4 mm in depth was surgically created in the corticocancellous bone of the metaphyseal part of the right tibia of each rat. No other application was made in this group during the experimental setup. For each rat in the high-fructose-fed defect group (n=12), cylindrical defects of 4 mm in diameter and 4 mm in depth were surgically created in the corticocancellous bone of the metaphyseal part of the right tibia. Fructose supplements of the groups were added to the drinking water at a rate of 20% (w/v).All rats were sacrificed at the end of the 12th week of the surgical application. The histological samples were evaluated under a light microscope. There was no significant differences in the bone regeneration between control animals and high fructose diet consumption group.52.2 +/- 9 % for Controls, versus 49.8 +/- 7.67 % for HFD (P>0,05).Further research is needed to determine the mechanisms responsible for these changes in bone structure and how these changes affect bone quality and strength with age.
Evaluación histopatológica de los efectos de una dieta alta en fructosa sobre la curación ósea en defectos tibiales: un estudio experimental
Keywords: Fructose; high fructose diet; bone healing; bone metabolism; bone formation